Influence of styrofoam-based additives on the mechanical properties of mortar for concrete roof tile production - Sudirman Indra; Adinda Yunita Putri; Mohammad Erfan; Vega Aditama; Redi Sigit Febrianto; Ratri Andinisari (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2026)
Concrete roof tile are widely used as roofing material due to its durability and performance. However, concrete roof tiles have relatively high weight and their production cost limit broader application. This study aims to develop an environmentally friendly lightweight concrete roof tile by adding styrofoam waste as a partial substitute for fine aggregates in the mortar mix. Four percentage variations of styrofoam content were used in making mortar and roof tile samples, which are 0%, 4%, 8%, and 12% relative to the total volume of sample. These variations were chosen to investigate the effect of styrofoam addition on the mechanical and physical properties of mortar and concrete roof tiles. A series of tests were also conducted, such as compressive, tensile, and flexural strength tests of mortar, flexural strength of roof tiles, as well as impermeability and porosity tests of the final products. The results of these tests indicate that the optimal mechanical performance was achieved at 8% styrofoam content, with mortar flexural strength reaching 5.05 MPa and roof tile flexural strength at 4.58 MPa. Although compressive strength declined with increasing styrofoam content, values remained within acceptable limits for non-structural applications. All roof tile samples met the impermeability criteria based on SNI 0096:2007, which states that there must not be water seepage through the samples for approximately 20 hours ± 5 minutes, regardless of their styrofoam content. Finally, it can be concluded that styrofoam can be effectively repurposed as an additive in concrete roof tile production, resulting in a lightweight, cost-effective, and sustainable building material.